Ambient polychlorinated biphenyl levels and their evaluation in a metropolitan city - Kuzu, S. Levent; Saral, Arslan; Summak, Gulsum; Coltu, Hatice; Demir, Selami (ELSEVIER SCIENCE BV, 2014)
In this study, summer and autumn ambient PCB concentrations were investigated in metropolitan city of Istanbul. 84 congeners were targeted from di-CBs to nona-CBs on both particle and gaseous phases. Gaseous ambient concentrations were determined to be 372 +/- 134 pg center dot m(-3), while on the particle phase this value was 49 +/- 17 pg center dot m(-3), corresponding to an average of 420 pg center dot m(-3). About one-tenth of all PCBs lay in ambient aerosols, while 90% of all comprise 2-, 3-, 4-, and 5-CBs. Measured ambient concentrations of each congener group were tested against meteorological data. The di-CB concentrations were independent of ambient temperature while northerly winds lead to an increase in their concentrations, which was an indicator of considerable contribution to di-CB concentrations from the medical waste incineration plant in Istanbul. In contrast, other congeners' concentrations were found to be correlated with southerly winds. Being an inland sea and having been contaminated, for years, by industrial discharges along the coastline, volatilization from Marmara Sea was considered as the most probable source of other congeners. PSCF analysis was run with 12-hour trajectories to locate possible local sources and ched< these results. Gas/particle partitioning was applied using three different models. m(r) and b(r) values for log P-L(0) model were determined as -0.23 +/- 0.09 and -3.25 +/- 0.38, respectively. For absorption based log K-oa model, m and b values were calculated as 0.23 +/- 0.08 and -4.73 +/- 0.83, respectively. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: PCB concentrations; MLR; PSCF; Gas/particle partitioning; POLYCYCLIC AROMATIC-HYDROCARBONS; AIR PARTITION-COEFFICIENT; GAS/PARTICLE CONCENTRATIONS; SOURCE APPORTIONMENT; ATMOSPHERIC PCB; ORGANOCHLORINE PESTICIDES; ORGANIC-COMPOUNDS; SOURCE LOCATIONS; INDUSTRIAL-AREA; DRY DEPOSITION; Environmental Sciences & Ecology